2001
DOI: 10.1097/00005392-200111000-00066
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Type Ii Receptor Expression and Ureteral Budding

Abstract: Although not the sole regulator, angiotensin type II receptor expression may have a role in the embryological development of the urinary tract by inhibiting aberrant ureteral budding. A defect in this inhibitory process appears to cause ectopic ureteral budding, and may subsequently lead to renal dysplasia and other congenital anomalies of the kidney and urinary tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 14 publications
0
30
0
5
Order By: Relevance
“…According to the developmental theory of VUR (24), ectopic ureteral budding results in defective vesicoureteral valve, resulting in VUR. Recent findings showed that ectopic budding occurs in angiotensin type II receptor (AT2) null mutant embryos (25). Angiotensin II has also been reported to regulate vascular endothelial growth factor (VEGF) synthesis at the initiation phase of translation of VEGF mRNA in proximal tubular epithelial cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…According to the developmental theory of VUR (24), ectopic ureteral budding results in defective vesicoureteral valve, resulting in VUR. Recent findings showed that ectopic budding occurs in angiotensin type II receptor (AT2) null mutant embryos (25). Angiotensin II has also been reported to regulate vascular endothelial growth factor (VEGF) synthesis at the initiation phase of translation of VEGF mRNA in proximal tubular epithelial cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no gold standard for measuring the position of the ureteric bud along the mesonephric duct (16,23). Miyazaki et al (19) looked at Bmp4ϩ/Ϫ mice and found a more cranially placed ureteric bud that they scored in relation to the nearest somite.…”
Section: Discussionmentioning
confidence: 99%
“…45 Studies have shown that induced obstruction in animal fetuses results in renal parenchymal abnormality, but presence of VUR was not determined. 46,47 The second theory proposes that abnormal ureteric budding and/or dysfunctional interactions between the ureteric bud and metanephric mesenchyme give rise to VUR and other renal abnormalities 48. Mouse embryo studies 38,49,50 demonstrate that abnormal ureteric budding was evident in many of the mice that developed renal tract anomalies. Investigators propose that abnormal budding explains the occurrence of VUR.…”
Section: Developmental Aspectsmentioning
confidence: 99%